YIA3 Proteomic analysis of the cardiac myofilament subproteome reveals dynamic alterations in phosphatase subunit distribution. Issue 17 (26th August 2010) - Yin, X; Cuello, F; Mayr, U; Hornshaw, M; Ehler, E; Avkiran, M; Mayr, M
Abstract : Rationale: Myofilament proteins are responsible for cardiac contraction. The myofilament subproteome, however, has not been comprehensively analysed thus far. Methods: Cardiomyocytes were isolated from rodent hearts and stimulated with endothelin-1 and isoproterenol, potent inducers of myofilament protein phosphorylation. Subsequently, cardiomyocytes were 'skinned' and the myofilament subproteome analysed using a high mass accuracy ion trap tandem mass spectrometer (LTQ Orbitrap XL) equipped with electron transfer dissociation. Results: As expected, a small number of myofilament proteins constituted the majority of the total protein mass, with several known phosphorylation sites being confirmed by electron transfer dissociation. More than 600 additional proteins were identified in the cardiac myofilament subproteome, including kinases and phosphatase subunits. The proteomic comparison of myofilaments from control and treated cardiomyocytes suggested that isoproterenol treatment altered the subcellular localisation of protein phosphatase 2A regulatory subunit B56α. Immunoblot analysis of myocyte fractions confirmed that β-adrenergic stimulation by isoproterenol decreased the B56α content of the myofilament fraction in the absence of significant changes in the myosin phosphatase target subunit isoforms 1 and 2 (MYPT1 and MYPT2). Furthermore, immunolabelling and confocal microscopy revealed the spatial redistribution of these proteins, with a loss of B56α from Z-disc and M-band regions but increased association of MYPT1/2 with A-band regions of the sarcomere, following β-adrenergic stimulation. Conclusion: We present the first comprehensive proteomic dataset of skinned cardiomyocytes and demonstrate the potential of proteomics to unravel dynamic changes in protein composition that may contribute to the neurohormonal regulation of myofilament contraction.